Factors Affecting Psychological Distress among People Living with HIV/AIDS at Selected Hospitals of North Shewa Zone, Amhara Region, Ethiopia - Elyas Admasu Basha; Behailu Tariku Derseh; Yohannes Gebre Egziabher Haile; Gedion Tafere (AIDS Research and Treatment)
Background. The new advances for the treatment of HIV infection using Highly Active Antiretroviral Therapy (HAART) have dramatically improved disease prognosis. However, they are living longer with a chronic condition that increases the risk for psychiatric and psychosocial problems. Various studies have linked HIV/AIDS with a number of psychological problems, depression being the most common. Moreover, studies have found that chronically ill people are at increased risk of psychological problems. Thus, this study aimed at assessing the level of psychological distress and its associated factors among people living with HIV/AIDS in selected Hospitals of North Sowa Zone of Amhara region, Ethiopia, 2017. Method. Institution based cross-sectional study design with systematic random sampling method was used. Data was collected by structured interviewer-based Amharic version questionnaire. A total of 422 people living with HIV/AIDS were involved in the study from 1 to 30 May 2017. Data analysis was done with the help of a computer program (SPSS version 16.0). Binary logistic regression analysis was used for bivariate and multivariate analysis. The strength of the association was presented by odds ratio with a 95% confidence interval. Result. The prevalence of psychological distress was 7.8% (95% CI: 5.25%, 10.39%). Being female (AOR = 3.02; 95% CI: 1.16, 7.82), illiterates (AOR = 3.91; 95% CI: 1.31, 6.45), participants who currently use alcohol (AOR = 2.70; 95% CI: 1.23, 5.88), respondents whose CD4 count is less than 500 cells/μl (AOR = 2.28; 95% CI: 1.02, 5.11), and participants who are considered stigmatized (AOR = 2.41; 95% CI: 1.11, 5.22) were positively associated with psychological distress. Conclusion. The prevalence of psychological distress was low as compared to other studies conducted in Ethiopia. This may affect the quality of life of people living with HIV/AIDS and their families. Being female, illiteracy, alcohol use, and having lower CD4 count and perceived stigma increased the odds of psychological distress. Thus, concerned stakeholders should collaborate on the integration of HIV/AIDs treatment and mental health services.